2022
DOI: 10.1038/s41586-021-04265-w
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of methicillin resistance predates the clinical use of antibiotics

Abstract: The discovery of antibiotics more than 80 years ago has led to considerable improvements in human and animal health. Although antibiotic resistance in environmental bacteria is ancient, resistance in human pathogens is thought to be a modern phenomenon that is driven by the clinical use of antibiotics1. Here we show that particular lineages of methicillin-resistant Staphylococcus aureus—a notorious human pathogen—appeared in European hedgehogs in the pre-antibiotic era. Subsequently, these lineages spread with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 64 publications
0
102
0
Order By: Relevance
“…A recently published study draws a similar conclusion. The authors postulate that wildlife represents a previously unrecognized medium through which environmental ARMGs can be transferred to human clinical pathogens [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study draws a similar conclusion. The authors postulate that wildlife represents a previously unrecognized medium through which environmental ARMGs can be transferred to human clinical pathogens [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and physiological functions of bacteria in biofilms are entirely different from those of planktonic bacteria free in suspension, allowing bacteria within biofilms to be upwards of 1000-fold more resistant to conventional antibiotic treatments and host immune responses as compared to the planktonic cells [4,5]. With the co-evolutionary adaptation of notorious human pathogens to hosts and the abuse of antibiotics in modern clinical medicine, intrinsic bacterial resistance to antibiotics has globally risen to a high-risk level [6]. Hence, efficient alternative therapeutic strategies are urgently needed to prevent pathogenic bacterial biofilm formation and control biofilm-based infections.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although antibiotic resistance is believed to arise primarily from human antibiotic overuse [ 15 ], a recent study [ 16 ] making use of time-resolved phylogenies suggested that particular lineages of mecC -MRSA appeared in European hedgehogs 200 years ago, i.e., more than a century before the first description of MRSA in humans. These lineages emerged in hedgehogs colonized with S. aureus and co-infected with a β-lactam-producer dermatophyte, Trichophyton erinacei .…”
Section: Introductionmentioning
confidence: 99%
“…These lineages emerged in hedgehogs colonized with S. aureus and co-infected with a β-lactam-producer dermatophyte, Trichophyton erinacei . The mecC -MRSA lineages developed to resist the penicillin produced by T. erinaceid and eventually spread within local hedgehog populations and between hedgehogs and secondary hosts, such as livestock and humans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%